2009
DOI: 10.1016/j.nut.2008.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of a neonatal low-protein diet in rats on the morphology of the larynx

Abstract: Macroscopic structures of the larynx are sensitive to short-term effects of a neonatal low-protein diet. Vocal cord development can be studied within the context of programming because their microscopic structures are sensitive to the long-term effects of a low-protein diet during lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is well established that LP intake, reduced FC and body weight gain during pregnancy/lactation are the three main factors influencing maternal and infant outcomes ( 31 33 ) . In fact, we have demonstrated that protein restriction during gestation produces intra–uterine growth restriction and continued protein restriction during lactation counteracts catch up growth and results in long-term decreases in body weight due to a reduction in both lean and fat mass ( 2 , 33 , 34 ) . The underlying probable mechanism of the deficit in an offspring’s growth patterns can be associated to hormonal alterations, such as reduced insulin-like growth factor-1 ( 35 ) concentration and growth hormone mRNA expression ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that LP intake, reduced FC and body weight gain during pregnancy/lactation are the three main factors influencing maternal and infant outcomes ( 31 33 ) . In fact, we have demonstrated that protein restriction during gestation produces intra–uterine growth restriction and continued protein restriction during lactation counteracts catch up growth and results in long-term decreases in body weight due to a reduction in both lean and fat mass ( 2 , 33 , 34 ) . The underlying probable mechanism of the deficit in an offspring’s growth patterns can be associated to hormonal alterations, such as reduced insulin-like growth factor-1 ( 35 ) concentration and growth hormone mRNA expression ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The body weight of pups was weekly recorded all through the experiment with a Marte Scale, AS-1000, approaching 0.01 g. The body length of pups was recorded on days 21-63 of life by measuring the external surfaces (nose-to-anus length) using a digital caliper (0.01 mm accuracy). The body weight and body length were used to determine the body mass index (BMI, grams/lengh 2 ) [ 17 ] .…”
Section: Off Spring Body Weight and Body Lengthmentioning
confidence: 99%
“…The body lengths of pups were recorded on days 21-63 of life by measuring the external surfaces (nose-to-anus length) using a digital caliper (0.01 mm accuracy). Body weight and body length were used to determine the body mass index (BMI, g/length 2 ) [17] .…”
Section: Offspring Body Weight and Body Lengthmentioning
confidence: 99%